John Locke : changing notions of government - Beumer, Robbert (2024)
The political idea of John Locke as “the father of liberalism” cannot be sustained. There is little to no resemblance to modern liberalism. That view is usually based upon his famous Two Treatises of Government (1689). It can be considered as his most coherent, and perhaps somewhat modern political theory. The same John Locke, however, wrote his first political theory in 1660 -1662. That was the so-called Two Tracts on Government. It is a defence of absolute and arbitrary rule by a magistrate. The main purpose of those two tracts is to argue against liberty of conscience, as part of a wider discussion on religious toleration. The tracts specifically focus on the moral status of the so-called things indifferent (adiaphora) within worship.